Korean Boy Group Fans in Indonesia: SNA Study #WE LOVE YOU JUNGKOOK vs #FULL ALBUM - Tri Nada Nisrina; Osly Usman (Journal of Economics, Business, and Government Challenges, 2021)
This study examines the role of #WE LOVE YOU JUNGKOOK and #FULL ALBUM onTwitter in shaping digital opinion support mobilization, measuring the comparison of networks,actors between hashtags, and digital opinion. The theory used is the Digital Movement ofOpinion by looking at the level of actors and the system. The research method is a quantitativecombination for communication networks with a sample of 5,000 tweet data: 2500 #WE LOVEYOU JUNGKOOK tweet data with 2964 actors, 1673 relationships and 2500 #FULL ALBUMtweet data with 2027 actors and 1478 relationships using netlytic with qualitative data to analyzethe text study and explain social networks. The results showed that #FULL ALBUM is morecapable of creating mobilization than #WE LOVE YOU JUNGKOOK.